Management of the Production Process of the Colombian Caribbean Coastal Cheese Supply Chain using Lean Manufacturing and Simulation in ProModel - Causado-Rodriguez, Edwin; Fernández, Andrés Mauricio Peñaloza; Mendoza, Jorge Luis Oyola (Journal of Ecohumanism, 2025)
Resource and production yield management in the Colombian Caribbean Coastal Cheese supply chain was carried out through the structuring of a lean manufacturing model and process simulation in Promodel. Production input variables such as raw milk, rennet, salt, equipment, times, processes, and allocations were evaluated in corresponding scenarios. Significant variations in production by department and cheese type were obtained. Scenario 4 stood out due to the increase in production achieved, as well as the improvement in production capacity and demand satisfaction. This model optimized resources and established minimum lead times, improving the efficiency and quality of the final product, and identifying bottlenecks such as milk availability. It was also important to manage its supply to avoid interruptions, providing a comprehensive view for decision-making and effective strategies in the value chain.